(untitled) - Atkinson, Anthony A (Upper Saddle River, N.J., 2004)
this text provides a balanced, cohesive integration of management and accounting that has been noticeably missing from current texts. This book appeals to the general business student as well as the Accounting major. It teaches how a business manager uses management accounting information to solve problems and manage activities within an organization. Accounting majors aspiring to become management accountants learn how to design and operate information systems that create value for their organizations. The entire text blends contemporary theory and the latest research in management accounting with practical applications and actual company experiences
Keywords: Managerial accounting,Kế toán quản trị